(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe coronary artery lesions on echocardiography and evaluate the short-term evolution of coronary artery lesions after IVIG administration Methods: This cross-sectional descriptive study included 35 patients diagnosed with Kawasaki disease and treated with IVIG at the Cardiology Department, Nghệ An Maternity and Pediatric Hospital, from August 1, 2023, to July 30, 2024. Results: In our study, the majority of cardiovascular lesions were mild coronary artery dilation. One patient could have inflammation in one or more coronary arteries at different levels. The most common location of coronary artery lesions was in the proximal segments of the left and right coronary arteries. The degree of coronary artery recovery depends heavily on the degree of dilation. In mild dilation, after 2 months of IVIG administration, most coronary arteries returned to normal. In moderate and giant dilation, it takes months or years for the coronary arteries to return to normal, and may even leave lifelong sequelae. Conclusion: The peak period of coronary artery dilation is from day 7 to day 10, mainly in the proximal segment. The degree of coronary artery dilation has a greater impact on recovery than the location and number of affected coronary arteries.